SIGNIFICANCE OF HEMATOLOGICAL PARAMETERS AS A DIAGNOSTIC TEST FOR MALARIA IN PATIENTS WITH ACUTE FEBRILE ILLNESS - DR.S.SAKTHI SELVA KUMAR M.D; DR.M.V.BHARGAVI, M.D; PROF.DR.S.PALANIANDAVAN, M.D (International Journal of Pharma and Bio Sciences, 2015)
The main objective of this study was Changes in complete blood count are among the most common complications encountered in malaria. This study evaluates those hematological changes as a diagnostic test for malaria in patients with acute febrile illness and to emphasize its usage for physician to institute specific antimalarial treatment. The present study conducted from June 2014 to June 2015. A total of 650 patients presenting with acute febrile illness at Sree Balaji medical college and hospital were evaluated. CBC and malarial parasite smear were done for each patient. 172 out of 650 patients (26.5%) were diagnosed to have malaria by positive smear. There were 121 males and 51 females with a male to female ratio of 2.3:1. There was a significant reduction in hemoglobin (p<0.005), platelet count (p<0.001) and total leukocyte count (p<0.001) levels malarial patients compared to those without the disease. A likelihood ratio for a positive result of platelets (6.2) and total leukocyte count (3.4) was relevant as compared to hemoglobin (1.61) and Red cell distribution width (1.79). The negative predictive values for hemoglobin (79%), total leukocyte count (86%), platelets (94%) and Red cell distribution width (93%) were significant. Red cell distribution width values were found to be higher in patients with malaria than in patients without malaria (p<0.001). This study showed that routinely lab findings such as hemoglobin, leukocytes, platelet counts and even red cell distribution width values can be used as a diagnostic clue in a patient with acute febrile illness, and hence giving the probability of malaria and as by prompting initiation of treatment.